A pilot study of attachment relationships, psychological problems and negative automatic thoughts among college students in Pakistan - Irfan, Siddrah; Zulkefly, Nor Sheereen (Walter de Gruyter GmbH, 2020)
Objectives: The present pilot study examined the associations between attachment relationships, psychological problems, and negative automatic thoughts among late adolescents in Rawalpindi, Pakistan. Subjects: A total of 98 participants (male = 49, female = 49) were recruited from government colleges in Rawalpindi, Pakistan. Methods: The measures used to assess the research variables of this cross sectional study were the Inventory of Parent-Peer Attachment (IPPA-Urdu), Depression, Anxiety, and Stress Scale (DASS-Urdu), and the Automatic Thought Questionnaire (ATQ-Urdu). Results: All of these measures had good reliabilities. Findings of the correlation analyses demonstrated that maternal, paternal and peer attachment relationships were negatively related to symptoms of depression and anxiety as well as to negative automatic thoughts. On the other hand, depressive and anxiety symptoms were positively associated with negative automatic thoughts. Additionally, findings suggested that future studies must investigate adolescents from two-parent households and exclude those with only one living parent. Conclusion: The results underscored the need for further investigations of the linkages between attachment relationships, negative automatic thoughts and psychological problems on larger samples.